The Bracegirdle affair : an episode in the history of the Lanka Sama Samaja Party - Muthiah, Wesley S.; Wanasinghe, Sydney (Colombo : Young Socialist Publication, 1998)
On the experiences of Mark Anthony Lyster Bracegirdle, b. 1912, an Englishman and his role in Sri Lankan politics.
Keywords: Lanka Sama Samaja Party -- History -- Sources; Trials (Sedition) -- Sri Lanka -- History -- Sources; Sri Lanka -- Politics and government -- 20th century -- Sources